Detection of the effect of PIT-1 gene genotypes on some productive traits in Holstein cattle - Marin Kadhim Mohammed Alzaydi; Abdullah Hameed Salim (University of Thi-Qar Journal of agricultural research, 2021)
The research was conducted at the Taj Al-Nahrain cattle station in Al-Diwaniyah governorate in Iraq on a sample of 85 Holstein cows imported from Germany, which were selected during the third season of milk production, in order to determine the genotypes of the PIT-1 gene and its relationship to a number of production traits. The PCR product (451bp) of the PIT-1 gene was digested using the Hinf1 restriction enzyme, and the digestion results showed that the studied genetic segment of the POU1F1 gene appeared in three genotypes (AA, AB, and BB) with percentages of 55.3, 42.6, 2.1%, respectively, and there were highly significant differences (P≤0.01) between the distribution of these percentages, and the A allele (0.766) was superior to the B allele (0.234). The results of the analysis of variance showed that the effect of the genotype of the POU1F1 gene on the characteristics of milk production (daily milk production, total milk production, peak production) was not significant except in the characteristic of peak milk production in favor of the BB genotype at a rate of 538.50 kg on each of the genotypes AA and AB while the results did not show a significant effect between the genotypes (AA, AB, BB) in both the daily milk production rate and the total milk production. It was found that the effect of the POU1F1 gene on body dimension traits (body length, frontal body height, posterior body height) was significant (P≤0.05) in body length in favor of the BB genotype (164 cm) on each of the genotypes AA and AB, at 157,780. and 156,347 cm, respectively, while there were no significant differences between the genotypes in the anterior height and posterior height of the body.